Which wavelength is the best for arterial pulse waveform extraction using laser speckle imaging?. (March 2016) - Vaz, Pedro; Pereira, Tânia; Figueiras, Edite; Correia, Carlos; Humeau-Heurtier, Anne; Cardoso, João
Abstract : Highlights: Improvement of laser speckle imaging devices by using macro-circulation data. Shorter wavelengths show better results than larger wavelengths. Image processing techniques have no influenced in pulse waveform extraction. Abstract: A multi-wavelengths analysis for pulse waveform extraction using laser speckle is conducted. The proposed system consists of three coherent light sources (532 nm, 635 nm, 850 nm). A bench-test composed of a moving skin-like phantom (silicone membrane) is used to compare the results obtained from different wavelengths. The system is able to identify a skin-like phantom vibration frequency, within physiological values, with a minimum error of 0.5 mHz for the 635 nm and 850 nm wavelengths and a minimum error of 1.3 mHz for the 532 nm light wavelength using a FFT-based algorithm. The phantom velocity profile is estimated with an error ranging from 27% to 9% using a bidimensional correlation coefficient-based algorithm. An in vivo trial is also conducted, using the 532 nm and 635 nm laser sources. The 850 nm light source has not been able to extract the pulse waveform. The heart rate is identified with a minimum error of 0.48 beats per minute for the 532 nm light source and a minimal error of 1.15 beats per minute for the 635 nm light source. Our work reveals that a laser speckle-based system with a 532 nm wavelength is able to give arterial pulse waveform with better results than those given with a 635 nm laser.